Biplane Fluoroscopic-Guided Balloon Rhizotomy for Trigeminal Neuralgia: A Technical Note. Issue 3 (24th June 2019) - Vance, Awais Z; El Ahmadieh, Tarek Y; Christian, Zachary; Aoun, Salah G; Barnett, Samuel L; White, Jonathan A
Abstract: BACKGROUND: The classic percutaneous technique used to cannulate the foramen ovale for the treatment of trigeminal neuralgia can place important anatomic structures, such as the distal cervical internal carotid artery, at risk. OBJECTIVE: To use fixed anatomic landmarks to safely and reliably locate the foramen ovale on anteroposterior (AP) fluoroscopy. METHODS: Locating the foramen ovale was initially tested using AP fluoroscopy on cadaveric skulls in the neurosurgical simulation lab. Fluoroscopic landmarks were identified and utilized to assist in successfully locating the foramen ovale during percutaneous balloon rhizotomy procedures in patients with trigeminal neuralgia. This technique has been successfully used in multiple patients. In this report, we describe our technique in detail. RESULTS: The AP fluoroscopy is directed laterally in the coronal plane until a line drawn inferiorly from the lateral orbital rim bisects the inner concavity of the mandibular angle. Fluoroscopy is then directed inferiorly until the top of the petrous ridge bisects the mandibular ramus. The foramen ovale will come into view within the window between the mandibular ramus and hard palate. Two case illustrations are provided. CONCLUSION: Balloon rhizotomy is a commonly used treatment option for trigeminal neuralgia. Direct visualization of the foramen ovale can reliably be achieved on AP fluoroscopy using specific anatomic landmarks. This technique can be utilized to increase the accuracy and safety of the procedure.